Bio prospecting of Riboflavin producing bacteria from different riboflavin enriched food sources (Bioscience Journal, 2022)
Riboflavin is an essential, water-soluble vitamin (B2) and a component of basic cellular metabolism. The aim of the present study is to isolate and characterize riboflavin producing bacteria from different food sources. Ten different riboflavin enriched food sources were collected from Vellore district. Totally 72 bacterial strains were isolated and cultured on nutrient agar plates. Out of these, 43 strains were identified as riboflavin producers. Isolated bacterial strains HDS27, HDS07, HDS14, HDS18, HDS38 and HDS54 isolated from milk, mushroom, spinach, lamb kidney, beef liver and mackerel fish were found to be potent riboflavin producers. Based on morphological, biochemical and molecular characterization, the potent strains were identified as Lactobacillus plantarum (HDS27), Bacillus cereus (HDS07), Delftia tsuruhatensis (HDS14), Citrobacter freundii (HDS18), Enterobacter cloacae (HDS38) and Bacillus cereus (HDS54). The selected potent isolates HDS27 from milk and HDS07 from mushroom showed a maximum riboflavin production of 3.69 mg/L and 2.9mg/L respectively. The present study explores the riboflavin producing novel bacteria from different food sources. This is the first report that the Enterobacter cloacae isolated from beef liver, Delftia tsuruhatensis from spinach and Citrobacter freundii from lamb kidney has the ability to produce riboflavin. These potent strains could be a better starter for substituting the conventional bacteria for large scale production of riboflavin in industry.